2005
DOI: 10.1002/ejic.200400663
|View full text |Cite
|
Sign up to set email alerts
|

(Cyanocyclopentadienyl)potassium and ‐cesium

Abstract: Abstract(Cyanocyclopentadienyl)potassium and ‐cesium have been synthesized and subsequently characterized by single‐crystal X‐ray structure determinations, 1H and 13C NMR spectroscopy in solution as well as by 133Cs NMR spectroscopy in solution and the solid‐state. Both salts crystallize in zigzag chains which are crosslinked differently through the cyano substituents. There is significant distortion of the cyanocyclopentadienide ion toward a fulvalene‐like structure because the alkali‐metal ions do not only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The extended Hückel calculations were carried out with the program package CACAO, version 4.0. [47] Materials: All reagents were commercially obtained except for the following, which were synthesized according to literature procedures: Li(C 5 Me 5 ), [48] K(C 5 H 4 CN), [18] Tl(C 5 H 4 CN), [17d] FeCl 2 ·1.5 THF, [49] NiBr 2 ·1.5 THF, [50] [FeCl(C 5 Me 5 )(tmeda)] (tmeda = N,N-tetramethylethylenediamine), [51] [Co(C 5 Me 5 )(acac)] (acac = acetylacetonate), [52] and [Ni(C 5 Me 5 )(acac)]. [53] The solvents were dried by standard methods and freed from dioxygen by distilling under a stream of dinitrogen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extended Hückel calculations were carried out with the program package CACAO, version 4.0. [47] Materials: All reagents were commercially obtained except for the following, which were synthesized according to literature procedures: Li(C 5 Me 5 ), [48] K(C 5 H 4 CN), [18] Tl(C 5 H 4 CN), [17d] FeCl 2 ·1.5 THF, [49] NiBr 2 ·1.5 THF, [50] [FeCl(C 5 Me 5 )(tmeda)] (tmeda = N,N-tetramethylethylenediamine), [51] [Co(C 5 Me 5 )(acac)] (acac = acetylacetonate), [52] and [Ni(C 5 Me 5 )(acac)]. [53] The solvents were dried by standard methods and freed from dioxygen by distilling under a stream of dinitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…[16] Because this reaction sequence would not be tolerated by the analogous cobaltocenes and nickelocenes without decomposition, we chose an alternative route starting from the [C 5 have been obtained [17] either from dicyclopentadienedicarboxylic acid or [C 5 H 5 ] À and ClCN, and we recently investigated KA C H T U N G T R E N N U N G (C 5 H 4 CN) and Cs-A C H T U N G T R E N N U N G (C 5 H 4 CN) in some detail. [18] As the use of the cesium salt has no advantages, TlA C H T U N G T R E N N U N G (C 5 H 4 CN) [17d] and KA C H T U N G T R E N N U N G (C 5 H 4 CN) were selected and were treated with iron(II), cobalt(II), and nickel(II) precursor compounds (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…19) [40]. This leads us to the coordination compounds of alkali metal ions with carbon donors, of which phenyl groups and cyclopentadienyl (Cp)-ligands are the most representative in the formation of extended structures.…”
Section: N-donor Ligandsmentioning
confidence: 99%
“…In these it is shown that the cyclopentadiene anion shows a great distortion to the fulvalene structure in which the negative charge formally resides on the N atom. 52 The first structural characterisation of a potassium N-heterocyclic carbene has been reported. 53 The author's subverted the potential rearrangement or dimerisation issues which have plagued previous attempts at isolation of this type of compound through the use of stabilising O-functionalised sidearms.…”
Section: Potassium Rubidium and Caesiummentioning
confidence: 99%